IMPLEMENTATION OF EMPLOYMENT SOCIAL SECURITY PROGRAM POLICY FOR INFORMAL SECTOR WORKERS IN GORONTALO CITY - Maryam Bokiu (LP2M Universitas Bina Mandiri Gorontalo, 2023)
The purpose of this study is to determine the implementation of the Social Security Employment program policies for informal sector workers in the city of Gorontalo and to find out what factors determine the success of the Social Security Program for Informal workers in the city of Gorontalo. This type of research used in research is a qualitative approach, data collection techniques in research using in-depth interviews, namely in-depth interviews to obtain the necessary data and carried out openly and direct observation on the research object to see empirical data related to the focus under study. Documentation, namely the collection of data in the form of written documents, photographs and pictures and other objects related to the focus of the research. The results of the research the implementation of the employment social security program policy in the city of Gorontalo has not been running optimally because there are several indicators in the process of increasing the number of participants consisting of planning, implementation and supervision that have not been implemented as expected. The factors that determine the success of the employment social security program for informal sector workers in the city of Gorontalo are resources, communication, bureaucratic structure, and disposition, all of which must be considered and as far as possible conditioned to support the success of the policy implementation process, so that the objectives can be achieved.